PENGEMBANGAN E-MODUL BERBASIS PENDEKATAN TEACHING AT THE RIGHT LEVEL TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PADA MATERI PELUANG KELAS VIII SMP - Dinda Aurielia Ftri; Syarifah Fadillah; Utin Desy Susiaty (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to develop an e-module based on the Teaching at the Right Level (TaRL) approach to enhance the mathematical problem-solving skills of 8th-grade students regarding the topic of probability. The study employs the Research and Development (R&D) method using the ADDIE model, which encompasses the stages of Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques included validation sheets, response questionnaires, mathematical problem-solving ability tests, and interviews. The research subjects were grade VIII students (Class VIII A) at SMP Negeri 12 Pontianak. The results indicate that the e-module achieved a validity score of 92.5%, placing it in the highly valid category. The practicality of the e-module was demonstrated by teacher and student response rates of 96% and 87.8%, respectively, falling into the highly practical category. Meanwhile, post-test results showed a score of 77%, classifying the module as effective. Interview findings further revealed that the e-module helped students understand the material in a more structured manner tailored to their individual abilities. Thus, the TaRL-based e-module is suitable for use in instruction, particularly for the topic of probability.